An Efficient Implementation of Acute Lymphoblastic Leukemia Images segmentation on the FPGA - ElDahshan, Kamal; Youssef, Mohammed; Masameer, Emad; A. Mustafa, Mohammed (European Journal of Applied Sciences, 2015)
In the medical field, image segmentation process is considered the most essential step in image analysis. In this work, the color segmentation for acute lymphoblastic leukemia images (ALL) is applied to segment each leukemia image into two clearly defined regions: blasts and background. The ALL segmentation process is based on hue channel (H) of HSV color space as a method in segmentation of WBC from its complicated background. This work presents an efficient framework for segmentation of ALL images on a reconfigurable logic platform using Simulink, MATLAB and Xilinx System Generator (XSG). This segmentation framework is implemented on a FPGA using basic Xilinx Blockset to minimize hardware resources and lower execution time to be suitable enough for medical applications. It is designed using XSG as DSP design tool that enables the use of Simulink models, implemented in VHDL and synthesized for three different Xilinx FPGA boards.